2014
DOI: 10.1210/me.2013-1286
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor and p38 Promote Osteogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: Hepatocyte growth factor (HGF) is a paracrine factor involved in organogenesis, tissue repair, and wound healing. We report here that HGF promotes osteogenic differentiation through the transcription of key osteogenic markers, including osteocalcin, osterix, and osteoprotegerin in human mesenchymal stem cells and is a necessary component for the establishment of osteoblast mineralization. Blocking endogenous HGF using PHA665752, a c-Met inhibitor (the HGF receptor), or an HGF-neutralizing antibody attenuates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Moreover, using phospho-p38α specific antibodies we found that HGF treatment rapidly activated and phosphorylated p38α in hMSC in a dose- and time-dependent manner 37 . Interestingly, HGF treatment of hMSC also induced an increase in protein levels of p38α, p38β, p38δ, and p38γ, with the peak at 24hrs post-HGF treatment 37 . An increase in p38α, p38β and p38γ RNA was also seen within 48hrs after HGF treatment, in contrast to a decrease in p38δ 37 .…”
Section: 2 Hgf/cmet Signaling Pathwaysmentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, using phospho-p38α specific antibodies we found that HGF treatment rapidly activated and phosphorylated p38α in hMSC in a dose- and time-dependent manner 37 . Interestingly, HGF treatment of hMSC also induced an increase in protein levels of p38α, p38β, p38δ, and p38γ, with the peak at 24hrs post-HGF treatment 37 . An increase in p38α, p38β and p38γ RNA was also seen within 48hrs after HGF treatment, in contrast to a decrease in p38δ 37 .…”
Section: 2 Hgf/cmet Signaling Pathwaysmentioning
confidence: 79%
“…Our group was the first to show that HGF treatment leads to the rapid activation of total p38 in hMSC 37 . Moreover, using phospho-p38α specific antibodies we found that HGF treatment rapidly activated and phosphorylated p38α in hMSC in a dose- and time-dependent manner 37 .…”
Section: 2 Hgf/cmet Signaling Pathwaysmentioning
confidence: 96%
See 3 more Smart Citations